Importance of Payment Balance for a Country's Investment - Maxmudjanova Malika Djamshiddinovna; Ilmiy rahbar: Achilov U. U. (Scientific Trends, 2024)
This article discusses investment, components, payment balance, its impact.
Keywords: Country development, investment processes, payment balance, foreign and international investment, capital trade balance.